2018
DOI: 10.1371/journal.ppat.1006950
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear RNA surveillance complexes silence HIV-1 transcription

Abstract: Expression from the HIV-1 LTR can be repressed in a small population of cells, which contributes to the latent reservoir. The factors mediating this repression have not been clearly elucidated. We have identified a network of nuclear RNA surveillance factors that act as effectors of HIV-1 silencing. RRP6, MTR4, ZCCHC8 and ZFC3H1 physically associate with the HIV-1 TAR region and repress transcriptional output and recruitment of RNAPII to the LTR. Knock-down of these factors in J-Lat cells increased the number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 29 publications
0
28
0
1
Order By: Relevance
“…1A). To validate the interaction of DDR factors with actively transcribed HIV-1, we performed chromatin immunoprecipitation (ChIP) in cells containing an integrated HIV-1 LTR linked to a luciferase reporter, as described previously (12). Tat These data indicated that DDR factors such as MDC1 and MRN may be closely linked with active transcription.…”
Section: Ddr Factors Are Associated With Active Transcriptionmentioning
confidence: 99%
See 3 more Smart Citations
“…1A). To validate the interaction of DDR factors with actively transcribed HIV-1, we performed chromatin immunoprecipitation (ChIP) in cells containing an integrated HIV-1 LTR linked to a luciferase reporter, as described previously (12). Tat These data indicated that DDR factors such as MDC1 and MRN may be closely linked with active transcription.…”
Section: Ddr Factors Are Associated With Active Transcriptionmentioning
confidence: 99%
“…Tandem affinity purification of Flag-HA MDC1 was performed, as described previously (12)(13)(14) ( Fig. 1B).…”
Section: Ddr Factors Are Associated With Active Transcriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cette inhibition résultait de la dégradation de l'ARN viral naissant par RRP6. Plus récemment, dans un manuscrit paru dans PLOS Pathogens [7] tant de souligner que seule la déplétion concomitante des deux protéines a permis d'activer la transcription du promoteur VIH-1 à un niveau comparable à celui des cellules n'exprimant plus RRP6. En revanche, l'extinction unique de ZCCHC8 ou de ZFC3H1 n'a pas eu d'effet majeur.…”
Section: Les Facteurs De L'exosome Nucléaire Répriment L'expression Dunclassified